A feasibility study using solution-focused coaching for health promotion in children and young people with Duchenne muscular dystrophy. (17th February 2018) - McPherson, Amy C.; McAdam, Laura; Keenan, Sarah; Schwellnus, Heidi; Biddiss, Elaine; DeFinney, Andrea; English, Kirsten
ABSTRACT: Purpose : To evaluate the feasibility and acceptability of a coaching intervention (Solution-Focused Coaching in pediatric rehabilitation [SFC-Peds]) related to physical activity and diet in males with Duchenne muscular dystrophy. Methods : A pre-post design was employed. Participants had five coaching sessions over 8 weeks. The first session was face-to-face, followed by four virtual sessions. Feasibility criteria included recruitment rates, attrition, and intervention fidelity. The Canadian Occupational Performance Measure (COPM) and Goal Attainment Scaling (GAS) were employed to look at outcome trends. The acceptability was assessed using a survey. Results : Five males (11–19 years) participated. All feasibility criteria were met. Clinically significant increases were observed for GAS and COPM scores. Participants reported SFC-Peds to be acceptable. Broad barriers and facilitators to coaching success were identified. Conclusions : A SFC-Peds intervention for health promotion is feasible and acceptable in children with DMD and their families. A rigorous efficacy study assessing SFC-Peds intervention is warranted.